BUSINESS MODELS FOR SMES IN BANDUNG: SWOT ANALYSIS - Machmud, Senen; Sidharta, Iwan (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2014)
The main objective of this study is to find the model business for small and medium-sized enterprises (SMEs) with management strategy and business strategy approach. This research to help researchers, owners of SMEs and government in developing a framework for management strategy and business strategy on how the best result of business models. This study is valuable considering the limited among of empirical work previously done on the topic in question. The result of management strategies is internal and external factor analysis than analysis with strength, weakness, opportunities, and treatment (SWOT). Keywords: model business; strategic management; business strategy; SWOT analysis; SMEs.